Quality of medical care from an bioethical point of view in an ophthalmological hospital in Mexico City - Romero Chávez, Edith; Contreras Estrada, Daniela; Cantú Quintanilla, Guillermo (Acta Bioethica, 2019)
Objective: To analyze the perception of the quality of medical care from a bioethical point of view. Methods: Cross-sectional, analytical, descriptive and quantitative study. We used two questionnaires to assess the perception of medical care regarding bioethical principles. We did a descriptive and bivariate analysis with each one of the variables, and we obtained a score of the questions related to the bioethical principles. Results: We included 252 participants and found that during medical care, the following principles were met: 14% Autonomy, 72% Beneficence, 51% Dignity, 30% Integrity, 42% Justice, 52% No Maleficence and 27% Vulnerability. 3% obtained all the bioethical principles. Conclusions: One of the significant challenges of medicine is the implementation of quality models of medical care, which guarantee that patients receive medical care that takes into account bioethical principles.